1983
DOI: 10.1099/0022-1317-64-10-2139
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Heterotypic Interference between Influenza A and B Viruses: A Differential Inhibition of the Synthesis of Viral Proteins and RNAs

Abstract: SUMMARYMixed infection of MDCK cells with influenza A and influenza B viruses leads to a reduction in the rate of synthesis of haemagglutinin (HA) and nucleoprotein (NP) as compared to their rate of synthesis in cells separately infected with these viruses. The reduction is much stronger for influenza A virus proteins. The synthesis of the nonstructural NS1 protein of both viruses is relatively resistant to the heterotypic interference. The synthesis of virus-specific mRNAs exhibits the same pattern: the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…Similar results were also described by Tobita & Ohori (1979), and preferential suppression of the expression of the HA and NP genes of influenza A virus has recently been reported by Kaverin et al (1983). We could not determine the inhibitory effect of B/Kanagawa on the synthesis of the A/WSN HA polypeptide, because of its poor incorporation of radioactive methionine.…”
Section: Ipsupporting
confidence: 72%
See 4 more Smart Citations
“…Similar results were also described by Tobita & Ohori (1979), and preferential suppression of the expression of the HA and NP genes of influenza A virus has recently been reported by Kaverin et al (1983). We could not determine the inhibitory effect of B/Kanagawa on the synthesis of the A/WSN HA polypeptide, because of its poor incorporation of radioactive methionine.…”
Section: Ipsupporting
confidence: 72%
“…In simultaneously co-infected cells, these polypeptides of both type A and type B viruses, except for NS of B/Kanagawa, were synthesized in reduced amounts (lane 2). A similar observation has been described by Kaverin et al (1983). When NP bands were cut from the gel and examined for their radioactivities, the results showed that the amounts of N P of A / W S N and B/Kanagawa in simultaneously co-infected cells were 27 ~ and 41 ~ respectively of those in singly infected cultures.…”
Section: Interference Between Influenza A/wsn and B/kanagawamentioning
confidence: 53%
See 3 more Smart Citations